Reduction of viral load and immune complex load on CD4+ lymphocytes as a consequence of highly active antiretroviral treatment (HAART) in HIV-infected hemophilia patients - Daniel, Volker; Süsal, Caner; Melk, Anette; Weimer, Rolf; Kröpelin, M.; Zimmermann, R.; Huth-Kühne, A.; Uhle, C.; Opelz, Gerhard (Immunology letters, 1999)
BACKGROUND AND OBJECTIVES: Human immunodeficiency virus (HIV)-induced immune complex load on circulating CD4+ blood lymphocytes is associated with dysfunction and depletion of CD4+ lymphocytes and with increased monocyte/macrophage function. It was investigated whether HAART reduces both the viral load in plasma and the number of immune complex-coated CD4+ lymphocytes in the blood, and whether CD4+ counts are associated with viral load and/or immune complex load. MATERIALS AND METHODS: Twelve HIV+ hemophilia patients before and after conversion to HAART (group 1); eight HIV+ hemophilia patients without antiretroviral therapy (group 2). HIV-1 RNA copies in plasma using NASBA/Nuclisens kits; CD4+ lymphocytes coated in-vivo with immune complexes using flowcytometry on whole blood samples; in-vitro responses of immune complex-coated T lymphocytes in cell culture assays. RESULTS: After conversion to HAART there was a significant reduction of viral load, CD4+ gp120+, CD4+ IgM+, and CD4+ IgG+ circulating blood lymphocytes and plasma neopterin, paralleled by a significant increase of CD4+ and CD8+ counts. The percentage of immune complex-coated CD4+ lymphocytes of converted patients was significantly associated with CD4+ counts, in-vitro responses to concanavalin A (Con A), pokeweed mitogen (PWM), phytohaemagglutinin (PHA), anti-CD3 and pooled allogeneic stimulator cells, and with plasma neopterin levels. CONCLUSION: HAART reduces viral load and HIV-induced immune complex load on circulating CD4+ blood lymphocytes. The results of this study can be interpreted to suggest that HAART increases CD4+ lymphocyte counts in part by counteracting HIV-induced autoimmune phenomena.